Respuesta :

Answer: Option A

Step-by-step explanation:

First let's rewrite our equation as:

f(x) = 0

We start with:

[tex]\frac{1}{2x + 1} + 1 = \sqrt[3]{x}[/tex]

Then we can rewrite this as:

[tex]\frac{1}{2x + 1} + 1 - \sqrt[3]{x} = 0[/tex]

Now we can graph an equation like:

[tex]y = f(x) = \frac{1}{2x + 1} + 1 - \sqrt[3]{x}[/tex]

And find the values of x such that the graph of this function intersects the x-axis, the graph can be seen below:

If you do some zoom, you can see that the intersections are at:

x ≈ -0.76

x ≈ 1.80

Then the correct solution is: Option A.

Ver imagen facundo3141592

The solution of equations are [tex]x=1.803[/tex] and [tex]x=-0.761[/tex]

Solution of equation:

Given equation is;

             [tex]\frac{1}{2x+1}+1=\sqrt[3]{x}[/tex]

We have to find the solution of the above equation.

           [tex]y=\frac{1}{2x+1}+1\\y=\sqrt[3]{x}[/tex]

The graph of both function shown in the the graph.

The intersection point of the graphs of both function will be the solution.

From graph, it is observed that intersection points are [tex](1.803,1.217)[/tex] and [tex](-0.761,-0.913)[/tex].

Hence, the solution of equations are [tex]x=1.803[/tex] and [tex]x=-0.761[/tex]

Learn more about the graph of function here:

https://brainly.com/question/24748644

Ver imagen ibiscollingwood
ACCESS MORE